Чреспищеводная электростимуляция в оценке предсердно-узлового проведения - Д. А. Швец (Архивъ внутренней медицины)
Transesophageal electric stimulation (TES) is a method of non-invasive cardiac electrophysiology studies. The aim of the study is to evaluate the possibility of TES in the research into atrio-nodal conductions. The scientific innovation is in a non-invasive analysis of the heterogeneity of the refractory period of atrio-nodal connections. 249 patients were examined. By the nature of AV-conduction curve the patients were divided into 2 groups. The first group (109 persons) consisted of the patients with diagnosed transition point (TP). The second group included 140 people, whose V1-V2 dependence of A1-A2 was close to a line — without a TP. It was discovered that the differences in atrio-nodal conductions depend on the effective refractory period of atrioventricular connection. A low index of ERP atrio-nodal conduction is more physiological and accompanied (ERP) by the absence of the increase heart rate under the most further increase the frequency atrial stimulation. A high index of ERP can be caused by different reasons. This variant of atrio-nodal conductions is followed by less favorable changes in hemodynamics.